Feasibility and effectiveness of global intact forest landscape protection through forest certification: the conservation burden of intact forest landscapes - Zwerts, Joeri A.; van der Linde, Chaia M.; Praamstra, Gijsbert J.; Schipper, Joep; Trolliet, Franck; Waeber, Patrick O.; Garcia, Claude A. (Frontiers in Forests and Global Change, 2024)
Intact Forest Landscapes (IFLs) are defined as forested areas of at least 500 km2 that show no signs of remotely sensed human activity. They are considered to be of high conservation value due to their role in maintaining biodiversity and mitigating climate change. In 2014, the members of the Forest Stewardship Council (FSC), one of the major global certification schemes for responsible forest management, took a conservation stand by restricting logging in FSC-certified IFLs. However, this move raised concerns about the economic viability of FSC-certified logging in these areas. To address these challenges, in 2022, FSC proposed an integrated landscape approach, considering local conditions and stakeholders' needs to balance IFL protection, economic sustainability, and community interests. This paper leverages publicly available management unit (MU) data, introducing the concept of 'conservation burden' for MUs overlapping with IFLs. It provides a global quantitative overview of IFLs designated for timber production and suggests a metric that can help design tailored solutions based on the extent of IFL overlap. The findings aim to facilitate stakeholder engagement for landscape-level solutions and discuss the implications for global responsible forest management.